Demographic profile and risk factors associated with dry eye disease in North Western Rajasthan, India - Jaju, Meenu; Jain, Kalpna; Kanawa, Surbhi (International Journal of Research in Medical Sciences, 2019)
Background: The aim was to study the demographic profile and analyze risk factor associated with dry eye disease in North West Rajasthan, India. Methods: This was a hospital-based study conducted in Department of Ophthalmology, Sardar Patel Medical College, Bikaner, Rajasthan. Sample size of this study was 100 patients. All participants underwent a general ophthalmic assessment including history of any previous ocular and systemic illness along with ocular examination on slit lamp and specific tests for dry eye (Schirmer's test and Tear film break up time) were performed. Results: Dry eye were seen maximum in age group 46 to 60 years (41%), followed by 61-75 years (23%). Female’s preponderance was seen compared with male. Dry eye patients belong from rural areas were (57%) while remaining (43%) from urban areas and among these highest were farmer/labourers (32%). Several known risk factors were found in this study which include post-menopause. Climatic condition like excessive wind, high temperature and computers users had strong association with dry eye. In Systemic disease rheumatoid arthritis was commonly associated with dry eye were. Smoking contact lens use were also associated with increased risk of developing dry eye. Conclusions: Dry eye disease are more common in older age group patients. Female’s preponderance were found in the study especially postmeopausal women. Dry eye disease are more common in patients belongs to rural areas. Risk factor associated with dry eye were Climatic condition like excessive wind, high temperature and computers users, systemic disease like rheumatoid arthritis Smoking, contact lens users.